Revolutionizing English Language Education: A Comparative Study of Synchronous and Asynchronous Learning Methods - Prasetya, Rizky Eka (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study investigates the effectiveness of synchronous and asynchronous learning methods in English language education. A mixed-methods approach combines quantitative and qualitative data to understand the blended learning intervention comprehensively. A comparative analysis was conducted on two learners who received English language instruction using synchronous or asynchronous methods. The findings suggest that both methods have their strengths and weaknesses, and the specific learning objectives and student needs should determine the choice of method. Synchronous learning promotes interaction and communication skills more effectively, while asynchronous learning is more suitable for self-paced learning and developing reading and writing skills. The study highlights the importance of adopting a blended approach that combines synchronous and asynchronous methods to maximize the benefits of digital technologies in English language education.